2022
DOI: 10.1111/jfbc.14169
|View full text |Cite
|
Sign up to set email alerts
|

Hawthorn extract inhibited the PI3k /Akt pathway to prolong the lifespan of Drosophila melanogaster

Abstract: HE is a natural extract with strong antioxidant capacity. Drosophila melanogaster was used to explore HE could delay aging in this study. We detected that 3 mg/ml HE could increase stress tolerance (heat, cold, starvation, oxidative stress), reduce intestinal dysfunction, and prolong the lifespan of D. melanogaster. Network pharmacology analysis showed HE could act through the PI3K‐Akt pathway. Meanwhile, HE intervention inhibited the gene expression of InR, PI3K, and Akt‐1, and further increased the gene expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…41 A previous study has demonstrated that the longevity of hawthorn extract in Drosophila melanogaster was regulated by the PI3K/AKT pathway. 37 In addition, chlorogenic acid 42 and epigallocatechin 43 mediated the longevity of C. elegans relies on the IIS pathway. In this study, HFE up-regulated the gene level of daf-16 and down-regulated the levels of daf-2 , akt-1 , and age-1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 A previous study has demonstrated that the longevity of hawthorn extract in Drosophila melanogaster was regulated by the PI3K/AKT pathway. 37 In addition, chlorogenic acid 42 and epigallocatechin 43 mediated the longevity of C. elegans relies on the IIS pathway. In this study, HFE up-regulated the gene level of daf-16 and down-regulated the levels of daf-2 , akt-1 , and age-1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were observed in Drosophila melanogaster treated with hawthorn extract. 37 The PI3K/AKT signaling pathway is a part of the insulin/ insulin-like growth factor-1 signaling (IIS) pathway, which is a crucial mechanism for regulating senescence. 38 DAF-2 is located upstream of AGE-1, an ortholog of the mammal insulin/IGF receptor, its down-regulation could increase the…”
Section: Papermentioning
confidence: 99%
“…Some attention has been attracted to the effects of dietary manipulations on the lifespan of D. melanogaster and other animals. [20][21][22][23][24] These previously published studies suggest that dietary induction may be beneficial in extending the lifespan of fruit flies or other animals.…”
Section: Introductionmentioning
confidence: 95%
“…reported that activation of individual AMPs, including statin in D. melanogaster , significantly extended the lifespan of the fruit flies. Some attention has been attracted to the effects of dietary manipulations on the lifespan of D. melanogaster and other animals 20‐24 . These previously published studies suggest that dietary induction may be beneficial in extending the lifespan of fruit flies or other animals.…”
Section: Introductionmentioning
confidence: 99%
“…The methods referred to our previous study [15] . On the 15 th , 30 th , and 45 th day, wild-type flies were moved to empty pipes and anesthetized with CO 2 .…”
Section: Food Intake and Body Weight Assaysmentioning
confidence: 99%